A microRNA Cluster-Lefty Pathway is Required for Cellulose Synthesis During Ascidian Larval Metamorphosis - Sun, Xueping; Zhang, Xiaoming; Yang, Likun; Dong, Bo (Frontiers in Cell and Developmental Biology, 2022)
Synthesis of cellulose and formation of tunic structure are unique traits in the tunicate animal group. However, the regulatory mechanism of tunic formation remains obscure. Here, we identified a novel microRNA cluster of three microRNAs, including miR4018a, miR4000f, and miR4018b in Ciona savignyi. In situ hybridization and promoter assays showed that miR4018a/4000f/4018b cluster was expressed in the mesenchymal cells in the larval trunk, and the expression levels were downregulated during the later tailbud stage and larval metamorphosis. Importantly, overexpression of miR4018a/4000f/4018b cluster in mesenchymal cells abolished the cellulose synthesis in Ciona larvae and caused the loss of tunic cells in metamorphic larvae, indicating the regulatory roles of miR4018a/4000f/4018b cluster in cellulose synthesis and mesenchymal cell differentiation into tunic cells. To elucidate the molecular mechanism, we further identified the target genes of miR4018a/4000f/4018b cluster using the combination approaches of TargetScan prediction and RNA-seq data. Left–right determination factor (Lefty) was confirmed as one of the target genes after narrow-down screening and an experimental luciferase assay. Furthermore, we showed that Lefty was expressed in the mesenchymal and tunic cells, indicating its potentially regulatory roles in mesenchymal cell differentiation and tunic formation. Notably, the defects in tunic formation and loss of tunic cells caused by overexpression of miR4018a/4000f/4018b cluster could be restored when Lefty was overexpressed in Ciona larvae, suggesting that miR4018a/4000f/4018b regulated the differentiation of mesenchymal cells into tunic cells through the Lefty signaling pathway during ascidian metamorphosis. Our findings, thus, reveal a novel microRNA-Lefty molecular pathway that regulates mesenchymal cells differentiating into tunic cells required for the tunic formation in tunicate species.